2015
DOI: 10.1177/2047487315617105
|View full text |Cite
|
Sign up to set email alerts
|

Burden of hypertension in China over the past decades: Systematic analysis of prevalence, treatment and control of hypertension

Abstract: Although there has been a slight improvement in rates for the treatment and control of hypertension, these rates were still suboptimal, especially for men and people living in rural areas. Low and middle-income provinces had a comparatively huge burden of hypertension, which is a considerable risk factor for reducing life expectancy. Our analysis may be helpful in generating a current overview of hypertension in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 17 publications
3
49
0
Order By: Relevance
“…The prevalence of hypertension in China has been rising rapidly during the past two decades [14,15]. Pooled data from 178 studies between 1999 and 2014 revealed that the overall prevalence was 28.9% [16]. Using the same data of 50,171 participants, our previous results demonstrated that the prevalence was 31.2% among men and 28.0% among women based on the JNC-7 guideline [10].…”
Section: Discussionmentioning
confidence: 86%
“…The prevalence of hypertension in China has been rising rapidly during the past two decades [14,15]. Pooled data from 178 studies between 1999 and 2014 revealed that the overall prevalence was 28.9% [16]. Using the same data of 50,171 participants, our previous results demonstrated that the prevalence was 31.2% among men and 28.0% among women based on the JNC-7 guideline [10].…”
Section: Discussionmentioning
confidence: 86%
“…Although population awareness and medical compliance for treating hypertension have improved with time, more effort is still needed to appropriately manage hypertension in underdeveloped countries . As an underdeveloped region of China, many residents in Jilin province suffer from poorly controlled hypertension due to unhealthy living habits (high dietary salt and fat intake, as well as high alcohol and cigarette consumption), lower health awareness, lack of medical compliance, and climate variability . Poorly controlled hypertension might be attributed to AAD development .…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is an important risk factor for the occurrence of stroke and stroke death in China [18,19]. The prevalence of hypertension is estimated to be up to 28.9% [20]. Moreover, the prevalence of hypertension also exhibits a trend of being high in the north and low in the south.…”
Section: Discussionmentioning
confidence: 99%